Antioxidant Activity of Avocado Folium (Persea americana M.) - Wusurwut, Fahriya; Hasnaeni, Hasnaeni; Waris, Risda (Hydrogen: Jurnal Kependidikan Kimia, 2024)
Free radicals can be formed through normal cell metabolism events, malnutrition and as a result of responses to external influences such as pollution and ultraviolet rays. Free radicals can cause premature aging, therefore antioxidants are needed to prevent premature aging. Avocado folium (Persea americana M.) contain secondary metabolite compounds, namely alkaloids, saponins, tannins, glycosides and flavonoids in the form of quercetin, where flavonoid compounds can act as antioxidants. This study aims to determine the antioxidant activity of avocado leaf extract (P. americana M), using the (2,2-dihphenyl-1-picrylhdrazil) (DPPH)  method. The sample used in this research was avocado folium obtained from Southeast Maluku, Maluku Province). DPPH method with a UV-Vis spectrophotometer at a wavelength of 514 nm. The antioxidant activity of ethanol extract of avocado folium in this test is 112.410 µg / mL. The results of this study show that avocado folium extract has moderate antioxidant activity.